SUBSTANTIVE POLICIES DAN PROCEDURAL POLICY PADA UU NOMOR 23 TAHUN 2004 SEBAGAI SUATU KEBIJAKAN PUBLIK - Roro Rina Antasari (SOL JUSTICIA, 2021)
Law number 23 of 2004 concerning the Elimination of Domestic Violence as a legal product with the aim of becoming a legal umbrella in resolving issues/problems of domestic violence in the community. However, in its implementation, it still encounters various legal problems. In other words, as a form of public policy, certain goals or actions that are oriented towards certain goals have not been maximally achieved. Through the approach of Substantive Policies and Procedural Policy, it was found that there are still deficiencies/weaknesses in the substance or content of the article as a result of the lack of parties involved in the formation of the law. Furthermore, in terms of policy procedures, the political configuration greatly influences the legal product. Although it is recognized that every content of a legal product will be largely determined by the political vision of the dominant group present when the law is working in the realm of policy procedures.